Adoption of Transplanting Machine among Rice Farmers in Maluku, Indonesia - Inta Prista Novembriyanty Damanik; Meilvis Elsworth Tahitu (Journal of Agricultural Extension)
The study analyzed the adoption level of the rice transplanting machine in Maluku, Indonesia and examined the factors that influence the adoption level;. The study locations were Waimital and Debowae villages as the centers of rice production in Maluku, with a total of 100 respondents from 1,361 farmers as the population. Data were obtained through direct interviews with respondents using questionnaire. Data were analyzed using simple tabulation, the Structural Equation Model, and qualitative descriptive.  The results showed that most farmers had a relatively high level of adoption (86%). Based on the SEM analysis results, the P-value between the adoption level of the rice transplanting machine and social characteristics of farmers, characteristics of the machine, and availability of supporting facilities were <0.05.  It means that the adoption level of the rice transplanting machine was influenced by the social characteristics of farmers, the characteristics of the machine, and the availability of supporting facilities. The strategies to increase the adoption of the machine were to improve the quality of social characteristics of farmers, fulfill all the characteristics of the machine, and provide supporting facilities for the optimal use of the machine.